In Vitro Screening of Stem Explants of In Situ Uv-B Irradiated Cowpea Varieties for Germplasm Storage - Rajendiran, K; Gowsalya, L; Sudha, J Sudaroli (International Journal of Applied Sciences and Biotechnology, 2016)
Even though seeds form the natural progenies of all sexually reproducing plants, change in climate makes it mandatory to device in vitro methods for selecting germplasm for conservation and regeneration. An experiment was conducted to induct callus in stem explants (nodal region from third node from top of canopy) harvested on 30 days after seed germination from in situ control and supplementary ultraviolet-B irradiated (UV-B = 2 hours daily @ 12.2 kJ m-2 d-1; ambient = 10 kJ m-2 d-1) three varieties of cowpea (Vigna unguiculata (L.) Walp.) viz. Gowmathi, Fola and NS-634 to assess their response to in vitro culture. Axillary bud initiation occurred only from GOWMATHI control stem explants, while callus induction occurred in GOWMATHI and FOLA control stem explants. Stem explants harvested from all the three UV-B stressed cowpea varieties did not proliferate callus. The nodal stem explants of the three varieties of cowpea are not the suitable materials for germplasm preservation for growing in UV-B elevated climate. Int J Appl Sci Biotechnol, Vol 4(1): 44-52